2020
DOI: 10.1155/2020/1984972
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Solvent‐Based Cold Patching Asphalt Mixture Based on Multiscale

Abstract: In order to prepare a kind of high-performance asphalt pavement pit repair material and extend the service life of the road, this paper starts from the microscopic view of the raw materials, uses infrared spectrum, four component analysis method, lying drop method, column wick technology principle, etc. to select the raw materials and determine the initial amount of the cold patching asphalt mixture, and optimizes the formula through the orthogonal test design and adhesion, cohesion, initial stage strength, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…The raw materials of CAM used in this research included the modifier, diluent, base asphalt, and mineral aggregate [ 14 ]. The specific selected types and corresponding indicators of each material can be found in the following section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw materials of CAM used in this research included the modifier, diluent, base asphalt, and mineral aggregate [ 14 ]. The specific selected types and corresponding indicators of each material can be found in the following section.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [ 13 ] presented a performance evaluation method for solvent-based cold-patching asphalt solutions and developed a new solvent-based cold-patching asphalt liquid (CAL) via the orthogonal design method; the CAL consisted of base asphalt, a diluent, a tackifier, a surfactant, and an anti-stripping agent. Huang et al [ 14 ] determined the initial amount of CAM through infrared spectroscopy, four-component analysis, lying down method, and column core technology principle then optimized the formula by the orthogonal test design. The results showed that the road performance of self-made CAM is well verified.…”
Section: Introductionmentioning
confidence: 99%
“…Ocasionando que su intervención sea de manera reactiva o como un mantenimiento de emergencia [1], [2] con la finalidad de dar movilidad al usuario y evitar accidentes. Realizar actividades de conservación de manera inoportuna implica la aceleración del deterioro de la estructura del pavimento, la reducción del periodo de diseño, la afectación al usuario con relación a parámetros como: seguridad vial, comodidad, aumento de combustible, deterioro vehicular, mayores tiempos de desplazamiento y aumentos en el costo de operación [3], [4], [5], [6], y el retraso en las actividades de mantenimiento en las vías durante el ciclo de vida del pavimento. Lo que incrementa en dos a tres veces los costos en comparación con las intervenciones oportunas de conservación [7].…”
Section: Introductionunclassified
“…Esta técnica, aunque busca aumentar la vida útil del pavimento, tiene tiempos prolongados de ejecución y cuenta con limitaciones respecto a la época de intervención, ya que no es posible utilizar esta técnica durante el periodo de lluvias. Además del suministro y retiro de materiales y maquinaria y el traslado de personal calificado [9], [15], [16], [17], [18], [19].…”
Section: Introductionunclassified
See 1 more Smart Citation